PL02: Double Sequential External Defibrillation for Refractory Ventricular Fibrillation: the DOSE VF pilot randomized controlled trial. (May 2020) - Cheskes, S.; Dorian, P.; Feldman, M.; McLeod, S.; Scales, D.; Pinto, R.; Turner, L.; Morrison, L.; Drennan, I.; Verbeek, P.
Abstract : Introduction: Despite recent advances in resuscitation, some patients remain in ventricular fibrillation (VF) after multiple defibrillation attempts during out-of-hospital cardiac arrest (OHCA). Vector change defibrillation (VC) and double sequential external defibrillation (DSED) have been proposed as alternate therapeutic strategies for OHCA patients with refractory VF. The primary objective was to determine the feasibility, safety and sample size required for a future cluster randomized controlled trial (RCT) with crossover comparing VC or DSED to standard defibrillation for patients experiencing refractory VF. Secondary objectives were to evaluate the intervention effect on VF termination and return of spontaneous circulation (ROSC). Methods: We conducted a pilot cluster RCT with crossover in four Canadian paramedic services and included all treated adult OHCA patients who presented in VF and received a minimum of three defibrillation attempts. In addition to standard cardiac arrest care, each EMS service was randomly assigned to provide continued standard defibrillation (control), VC or DSED. Services crossed over to an alternate defibrillation strategy after six months. Prior to the launch of the trial, 2, 500 paramedics received in-person training for VC and DSED defibrillation using a combination of didactic, video and simulated scenarios. Results: Between March 2018 and September 2019, 152 patients were enrolled. Monthly enrollment varied from 1.4 to 6.1 cases per service. With respect to feasibility, 89.5% of cases received the defibrillation strategy they were randomly allocated to, and 93.1% of cases received a VC or DSED shock prior to the sixth defibrillation attempt. There were no reported cases of defibrillator malfunction, skin burns, difficulty with pad placement or concerns expressed by paramedics, patients, families, or ED staff about the trial. In the standard defibrillation group, 66.6% of cases resulted in VF termination, compared to 82.0% in VC and 76.3% of cases in the DSED group. ROSC was achieved in 25.0%, 39.3% and 40.0% of standard, VC and DSED groups, respectively. Conclusion: Findings from our pilot RCT suggest the DOSE VF protocol is feasible and safe. VF termination and ROSC were higher with VC and DSED compared to standard defibrillation. The results of this pilot trial will allow us to inform a multicenter cluster RCT with crossover to determine if alternate defibrillation strategies for refractory VF may impact patient-centered, clinical outcomes